The Surviving Sepsis Campaign: Research Priorities for Coronavirus Disease 2019 in Critical Illness. Issue 4 (April 2021) - Coopersmith, Craig M.; Antonelli, Massimo; Bauer, Seth R.; Deutschman, Clifford S.; Evans, Laura E.; Ferrer, Ricard; Hellman, Judith; Jog, Sameer; Kesecioglu, Jozef; Kissoon, Niranjan; Martin-Loeches, Ignacio; Nunnally, Mark E.; et al.
Abstract : OBJECTIVES: To identify research priorities in the management, pathophysiology, and host response of coronavirus disease 2019 in critically ill patients. DESIGN: The Surviving Sepsis Research Committee, a multiprofessional group of 17 international experts representing the European Society of Intensive Care Medicine and Society of Critical Care Medicine, was virtually convened during the coronavirus disease 2019 pandemic. The committee iteratively developed the recommendations and subsequent document. METHODS: Each committee member submitted a list of what they believed were the most important priorities for coronavirus disease 2019 research. The entire committee voted on 58 submitted questions to determine top priorities for coronavirus disease 2019 research. RESULTS: The Surviving Sepsis Research Committee provides 13 priorities for coronavirus disease 2019. Of these, the top six priorities were identified and include the following questions: 1) Should the approach to ventilator management differ from the standard approach in patients with acute hypoxic respiratory failure?, 2) Can the host response be modulated for therapeutic benefit?, 3) What specific cells are directly targeted by severe acute respiratory syndrome coronavirus 2, and how do these cells respond?, 4) Can early data be used to predict outcomes of coronavirus disease 2019 and, by extension, to guide therapies?, 5) What is the role of prone positioning and noninvasive ventilation in nonventilated patients with coronavirus disease?, and 6) Which interventions are best to use for viral load modulation and when should they be given? CONCLUSIONS: Although knowledge of both biology and treatment has increased exponentially in the first year of the coronavirus disease 2019 pandemic, significant knowledge gaps remain. The research priorities identified represent a roadmap for investigation in coronavirus disease 2019. Abstract : Supplemental Digital Content is available in the text.